2014
DOI: 10.1785/0120140032
|View full text |Cite
|
Sign up to set email alerts
|

Seismic-Wave Attenuation Determined from Tectonic Tremor in Multiple Subduction Zones

Abstract: Tectonic tremor provides a new source of observations that can be used to constrain the seismic attenuation parameter for ground-motion prediction and hazard mapping. Traditionally, recorded earthquakes of magnitude ∼3-8 are used to develop ground-motion prediction equations; however, typical earthquake records may be sparse in areas of high hazard. In this study, we constrain the distance decay of seismic waves using measurements of the amplitude decay of tectonic tremor, which is plentiful in some regions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…These values range between −1.0 and 0.6 log 10 units. Figure shows a histogram of all path correction terms that displays a distribution skewed to larger values as previously reported by Yabe et al [] for tremor data.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…These values range between −1.0 and 0.6 log 10 units. Figure shows a histogram of all path correction terms that displays a distribution skewed to larger values as previously reported by Yabe et al [] for tremor data.…”
Section: Resultssupporting
confidence: 60%
“…It is conceivable that strong along‐path attenuation might produce pulse broadening similar to that in Figure if LFE corner frequencies for the range of nominal magnitudes M W =1.0–2.6 were markedly higher than the observation pass band of 1–8 Hz. We consider this possibility unlikely since (i) seismograms of intraslab events with overlapping and longer paths retain significant energy to frequencies of 40 Hz or more and (ii) attenuation modeling of tremor and intraslab events in Cascadia and other subduction zones has shown that the latter are more severely attenuated than the former due to their additional transit through a low‐ Q layer at the top of the subducting plate [ Yabe et al , ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the amplitude of tremor is generally small and varies only slightly with size [ Vidale et al ., ], we set a threshold of 500 nm/s to separate tremor from earthquake signals. This empirical amplitude threshold is based on visual examinations of tremor waveforms during the 6 month (January 2010 to June 2010) period, resulting in an average of 251 ± 136 nm/s, similar to the amplitudes from another study [ Yabe et al ., ]. After applying the amplitude criterion, we rejected another 2640 events.…”
Section: Automatic Tremor Detection Proceduresmentioning
confidence: 99%